International and language education for a global future : fifty years of U.S. Title VI and Fulbright-Hays programs - Wiley, David, 1935-; Glew, Robert S. (Michigan State University Press, 2010)
The contributions to this book address the role that the U.S. Department of Education Title VI and Fulbright-Hays programs have played in building the largest and highest quality infrastructure in the world for training in languages and other aspects of foreign area knowledge. The volume celebrates the 50th anniversary of the Title VI and associated Fulbright-Hays programs, which have established more than 150 centers of excellence for modern foreign language and area studies and international business education in more than 60 U.S. universities. The authors review the histo.